Investigating drag reduction using turbolence altering pseudo-surface (TAPS) - Ashwin Charles, Benedict (2014)
The issue of drag reduction in pipes has already been widely researched and studied. Currently the most popular method for reducing drag in pipes employed commercially is through the use of additives. However, these additives do have drawbacks such as mechanical degradation, altering the chemical and physical properties of the fluid they inhabit as well as being toxic and non-biodegradable for the most part. This has spurred new research aimed to exploring more nature friendly, non-additive means of drag reduction. Among these techniques the most popular ones include riblets, dimples,oscillating walls, compliant surfaces and microbubles but each of these techniques have their respective drawbacks especially when considered for drag reduction in pipes. The present study introduces a novel non-additive technique that employs narrow strips of flexible elastic material in an arrangement mimicking the tentacles of a squid. This form of biomimickry has been frequent among the non-additive methods mentioned previously. The device which has been named the Turbulence Altering Pseudo-Surface (TAPS) consisted of 12 strips of elastic material (neoprene and silicone were tested in this study) of varying lengths of 0.2m, 0.3m, 0.4m, 0.5m, 0.6m and 0.7m with 0.005m width and 0.003m thickness each. The %DR was measured across 4 different testing section lengths, 0.5m, 1.0m, 1.5m and 2.0m spans. The flowrates tested were 6.0m /h, 6.5m 3/h, 7.0m 3/h,.5m 3/h, 8.0m 3/h, 8.5m 3/h, 9.0m 3/h and 9.5m 3/h. The results of the series of experiments carried out were both stimulating and intriguing. On one hand, the maximum %DR achieved is 65% with TAPS made of 0.6m strips of neoprene, but this is followed by an immediately negative pressure gradient change across the consecutive testing sections. On the other hand for TAPS made of 0.7m silicone strips, there is a peak recorded at 42.7% DR with considerable persistence of effect further downstream across the proceeding testing sections. These results raise a perplexing question of whether a localized high %DR is preferred or if a smaller but persisitent effect is better for flow improvement purposes. Whichever the case, this research has profound and important implications for the future of drag reduction in pipes as it has dispelled one of the age old myths, that reducing the effective pipe diameter always results in an increase in drag. There is immense potential in this field of research and plenty of room for improvement in future works.